Germanistik in Maribor = Germanistika v Mariboru: Tradition und Perspektiven = tradicija in perspektive - Marina Bajić; Jesenšek, Vida (2017)
German Studies in Maribor: Tradition and Perspectives. Tradition and perspectivesIn 2015 the Department of German Studies at the Faculty of Arts, University of Maribor, celebrated its 50th anniversary. On April 16, 2015 we commemorated this anniversary with a festive event, at which the professors and students of the department aswell as invited guest lecturers presented diverse views on German Studies as an academic and scientific discipline in modern times aswell as ponder about the past, present and future of learning and teaching German as a foreign language. Apart from this festive meeting we also prepared a retrospective exhibition about the history and thematic diversity of German Studies at the University of Maribor and organized a summer school entitled Alltag regional, which took place between June 29th and July 10th, 2015. The jubilee monograph, dedicated to the 50th anniversary of German Philology at the University of Maribor, brings reflection on the past, present and future of German Studies, on the theory and practice of German philology at universities outside of German speaking countries, but it also includes scientific articles from various fields of German linguistics, German literary science and the Didactics of German as a foreign language. The authors of the articles are staff members and students of the Department of German Studies at the Faculty of Arts, University of Maribor and colleagues from abroad. The monograph is divided into two parts: the first part offers a critical analytical view of the impact of the Bologna process on German Studies programs and the status of German Studies in university education; it contains six articles in which the authors write about the European tradition and future perspectives, the student experiences and ponder about the meaning and sense aswell as the integration of German Studies programs in the environment. The second part contains scientific articles from various fields of modern German Studies. The articles are ordered alphabetically by the names of the authors and they tackle lexicographical, methodical-didactic, stylistical, paremiological, sociolinguistic, morphological and word formation issues, discussđ the modern higher education policy and analyze selected German literary texts. The jubilee monograph offers an insight into the varied and changing 50-year-history of German Studies in Maribor and bears witness to the broad spectrum of the contemporary research in the field of German language and literature at the University of Maribor and elsewhere.
Keywords: University of Maribor; German studies; German linguistics; German literature studies; DaF-didactics